Effects of High-k Dielectric Materials on Electrical Performance of Double Gate and Gate-All-Around MOSFET - Kosmani, Nor Fareza; A. Hamid, Fatimah; Razali, M. Anas (International Journal of Integrated Engineering, 2020)
This paper presents the electrical behaviour of Double Gate (DG) and Gate-All-Around nanowire (GAA) MOSFET using different high permittivity (high-k) gate dielectric materials. In order to study the influence of high-k dielectric material towards DG and GAA, Atlas Silvaco TCAD tools were used to simulate the device and to determine the electrical characteristics. The high-k materials chosen in this study were Silicon Nitride (Si3N4), Aluminium Oxide (Al2O3), Zirconium Oxide (ZrO2) and Hafnium Oxide (HfO2). The gate dielectric materials have played a significant role in the design of novel and high performances at nanoscale of electrical devices. It can be observed that when approaching a higher value of dielectric constant, the on current increases while the subthreshold slope (SS) threshold voltage (Vth) and leakaga current reduced. It can be observed that HfO2 shows the best performance compared to other simulated dielectric materials for both DG and GAA MOSFET.